Gastroesophageal junction Paneth cell carcinoma with extensive cystic and secretory features - case report and literature review - Wenyi Luo; Wayne L. Hofstetter; Dongfeng Tan (BMC, 2019)
Abstract Background Carcinomas composed predominantly or purely of malignant Paneth cells were rarely reported in gastrointestinal system. They have not been reported at gastroesophageal junction nor has the association with Barrett esophagus been explored. None of the previous studies has mentioned any peculiar histologic features other than typical adenocarcinoma containing neoplastic Paneth cells. The Her2/neu status and the expression of beta-catenin in Paneth cell carcinoma at gastroesophageal junction have not been studied although the activated beta-catenin pathway was recently demonstrated in neoplastic Paneth cells in colon. Case presentation A 70-year-old Caucasian male who initially presented in the emergency room due to upper gastrointestinal bleeding was subsequently found to have a submucosal nodule at gastroesophageal junction. A diagnosis of adenocarcinoma was rendered on biopsy. Histologic examination of the subsequent endoscopic mucosal resection revealed an adenocarcinoma with various levels of differentiation which are zonally distributed. The deeper portion of the tumor showed well-differentiated bland-appearing glands with extensive cystic and secretory changes. The cytoplasm of tumor cells and secretion demonstrated marked reactivity with lysozyme antibody on immunohistochemical stain. The tumor had a peculiar Her2/neu staining pattern with cytoplasmic and nuclear stain in poorly-differentiated area and no stain in well-differentiated area. Only membranous stain was detected with beta-catenin antibody. Conclusion We reported the first case of Paneth cell carcinoma at gastroesophageal junction. The tumor had well-differentiated area which, when sampled in small biopsies, can mimic benign lesions including those related to proton pump inhibitor therapy. Lysozyme immunohistochemical stain may be helpful when difficulty in diagnosis arises. Her-2/neu was negative but showed a distinct staining pattern. In contrast to neoplastic Paneth cells in colon, beta-catenin pathway did not seem to be activated. More studies are needed for the etiology, pathogenesis, clinical course, prognosis and treatment of Paneth cell carcinoma.